IDENTIFIKASI DAN FAKTOR PENYEBAB CEDERA LEG LENGTH DISCREPANCY (LLD) PADA ATLET SEPAK TAKRAW SULAWESI TENGAH - Marhadi, Marhadi; Kristanti, Delvi Liloi; Sardiman, Sardiman (Dharmas Education Journal (DE_Journal), 2023)
Long legs on one side or called Leg Weight Discrepancy (LLD) is a condition where there is a difference in the length of the lower extremities (legs) from one another. LLD can occur in athletes caused by intrinsic and extrinsic factors. The purpose of this study is to identify the types of LLD and the factors that cause injuries to Central Sulawesi sepak takraw athletes. This study employs a descriptive methodology and a quantitative research design. The research subjects were 24 athletes. Results that will be generated in the form of scholarly articles published in National Journals with accreditation / National Proceedings. They orient the target of this research towards Athletes. The data collection technique uses a questionnaire as the instrument, to determine LLD by measuring the length of the right and left leg using the true leg length technique. Therefore, it is anticipated that this research will be completed to 100% so that coaches and athletes can use it to inform their training. Most of the Central Sulawesi Sepak Takraw Athletes suffered LLD injuries of 68.75% (11 athletes), while those who were not injured or normal were 31.25% (5 athletes). Intrinsic factors account for 52.14% of the factors that cause injuries that frequently affect athletes from Sepak Takraw and extrinsic factors of 47.86% with the following description: regulatory factors and the character of the sport with a percentage of 19.50%, then physiology at 18.91%, social at 16.69%, psychology along with tools and facilities at 16.54%, and factors causing injury due to weather as the least common cause of injury, which is 11.82%.